Ultrasensitive Change in Nucleosome Binding by Multiple Phosphorylations to the Intrinsically Disordered Region of the Histone Chaperone FACT. Issue 16 (24th July 2020) - Aoki, Daisuke; Awazu, Akinori; Fujii, Masashi; Uewaki, Jun-ichi; Hashimoto, Manami; Tochio, Naoya; Umehara, Takashi; Tate, Shin-ichi
Abstract: Facilitates chromatin transcription (FACT) is a histone chaperone that functions as a nucleosome remodeler and a chaperone. The two subunits of FACT, Spt16 and SSRP1, mediate multiple interactions between the subunits and components of the nucleosome. Among the interactions, the role of the DNA-binding domain in SSRP1 has not been characterized. We reported previously that the DNA-binding domain in Drosophila SSRP1 (dSSRP1) has multiple casein kinase II phosphorylation sites, and the DNA binding affinity of the domain changes sigmoidally in response to the degree of phosphorylation ("ultrasensitive response"). In this report, we explored the molecular mechanisms for the ultrasensitive response of the DNA-binding domain in dSSRP1 using the shortest fragment (AB-HMG, residues 434–624) responsible for nucleosome binding. AB-HMG contains two intrinsically disordered (ID) regions: the N-terminal part rich in acidic residues (AID) and the C-terminal part rich in basic residues (BID) followed by the HMG box. NMR and coarse-grained molecular dynamics simulations revealed a phosphorylation-dependent change in intramolecular contacts between the AID and BID-HMG, which is mediated by a hinge bending motion of AB-HMG to enable the ultrasensitive response. Ultrasensitivity generates two distinct forms of dSSRP1, which are high- and low-affinity nucleosome-binding forms. Drosophila FACT (dFACT) switches function according to the degree of phosphorylation of the AID in dSSRP1. We propose that dFACT in various phosphorylation states functions cooperatively to facilitate gene regulation in the context of the chromatin. Graphical abstract: Unlabelled Image Highlights: IDR in the DNA binding domain of FACT has multiple phosphorylation sites. DNA binding activity sigmoidally changes by the number of phosphates in the IDR. Intramolecular residue contact in the IDR achieves the sigmoidal activity change The sigmoidal DNA binding activity change explains the two-face functions of FACT